Nutritional status of geologically different vineyards in Helderberg - Shange, Philisiwe Lawrancia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MscAgric (Viticulture and Oenology))--University of Stellenbosch, 2009.